Dampak Pembuangan Sampah di Pesisir Pantai Mola, RT 01, RW 01, Terhadap Lingkungan Sekitar Masyarakat Mola Kelurahan Welai Timur - Baharia Kasim; Melki Immamastri Puling Tang; Nehemia Fanpada; Jon Abraham Lalang Yame; Depopamia Laupada (Yayasan Literasi Sains Indonesia, 2023)
Garbage is something that is produced from human activities and then it is not used and then thrown away. Coastal waste has become a global problem and is an issue that is being widely discussed. This is because coastal waste has an impact on the environment, economy and human health. In addition, the behavior of the community in disposing of waste on the coast is also a habit that can have a negative impact. To be able to overcome the waste problem, three aspects are needed, namely the government, society, and waste management procedures. This study aims to determine the impact of waste disposal on the coast to the surrounding environment. The type of research used in this study is a descriptive research type with a qualitative approach that refers to data in the form of words that have clear and definite characteristics. The results of this study also show that the behavior of coastal communities influences environmental damage. This is also influenced by the low level of public education about the Mola coastal area. The government can work together with the community to save Mola Beach from environmental damage caused by people's behavior.